Foreign-Born Teaching Assistants and the Academic Performance of Undergraduates - Borjas, George J (American Economic Review, 2000)
The large literature that analyzes the impact of immigration on the United States typically focuses on measuring the labor market and fiscal consequences. This literature, however, has ignored the impact of immigration on other sectors of society. One sector that is of great interest is the American university, where the share of nonresident aliens in the graduate student population rose from 5.5 percent in 1976 to 10.5 percent in 1996. Despite the rapid growth in the number of foreign students, little is known about their impact on the educational process. Nevertheless, undergraduates frequently complain that the lack of English language proficiency among many foreign-born Teaching Assistants affects adversely their understanding of the material. This paper addresses the question that is at the heart of these complaints: Do foreign-born teaching assistants have an adverse impact on the scholastic achievement of American undergraduates? To provide empirical evidence on this issue, I use data drawn from a survey of undergraduates enrolled in economics principles classes at a large public university. The data suggest that foreign-born Teaching Assistants have an adverse impact on the class performance of undergraduate students.